The concept of Mudarabah investment deposit - Hassan, Rusni; Abdul Aziz Bello, Shafi'i (TJPRC Pvt.Ltd., 2014)
Islamic finance is emerging as a rapidly growing part of the financial sector in the Islamic world as it has become a global phenomenon. Moreover, both Islamic and western countries have been embraced it. The mudarabah contract refers to an agreement made between a capital provider and another party who acts as the entrepreneur. Therefore, this paper attempts to analysis the concept of mudarabahin investment deposit. The characteristics of Investment deposit in both banks was briefly explained while its classification critically analysis. Furthermore, the mudarabah deposit and its categories mainly clarify. Also, the essential elements, condition of mudarabah and calculation of profit were elicited. In addition, the basis from primary and secondary sources was given to authenticate the practice of mudarabah. The explanation of guarantee returned in mudarabah, administrative costs, indirect expenses, modus operandi as well as difference between mudarabah and musharakah were shortly enlightened. It concluded with results.